2019
DOI: 10.1126/scisignal.aav3810
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the origin and evolution of pseudokinases across the tree of life

Abstract: Protein phosphorylation by eukaryotic protein kinases (ePKs) is a fundamental mechanism of cell signaling in all organisms. In model vertebrates, ~10% of ePKs are classified as pseudokinases, which have amino acid changes within the catalytic machinery of the kinase domain that distinguish them from their canonical kinase counterparts. However, pseudokinases still regulate various signaling pathways, usually doing so in the absence of their own catalytic output. To investigate the prevalence, evolutionary rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
144
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(156 citation statements)
references
References 148 publications
5
144
0
Order By: Relevance
“…We first removed 55 pseudokinases from the alignment. Following Kwon et al 23 , these proteins were identified by substitutions in one or more of the three conserved residues crucial for catalysis -DFG-Asp, HRD-Asp and β3-Lys. We then identified the highly conserved residue positions across kinases by the columns which are occupied by the same residue in at least 400 kinases in our MSA (90% of sequences).…”
Section: Structural Validation Of the Msamentioning
confidence: 99%
See 1 more Smart Citation
“…We first removed 55 pseudokinases from the alignment. Following Kwon et al 23 , these proteins were identified by substitutions in one or more of the three conserved residues crucial for catalysis -DFG-Asp, HRD-Asp and β3-Lys. We then identified the highly conserved residue positions across kinases by the columns which are occupied by the same residue in at least 400 kinases in our MSA (90% of sequences).…”
Section: Structural Validation Of the Msamentioning
confidence: 99%
“…for our MSA. We have also compared the quality of our alignment with the previously published alignments by Manning et al5 , Möbitz16 , Kwon et al23 , a hidden Markov model (HMM) derived from our MSA, and the initial ClustalOmega alignment. The average TPR for our MSA is 0.97, which is significantly better than the Möbitz (0.88), Kwon (0.90), and Manning (0.80) MSAs.…”
mentioning
confidence: 99%
“…The human kinome 5 includes ~50 pseudokinases that lack one or more residues generally required for catalytic activity. These residues include the ATP -binding lysine (K) within the VAIK motif, the catalytic D within the HRD motif and the magnesium binding D within the DFG motif 19 . Many pseudokinases function in signal transduction despite the absence of key catalytic residues.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that FN3Ks belong to a large super-family of protein kinase-like (PKL) enzymes that include eukaryotic protein kinases, small molecule kinases, and atypical kinases (21,22). FN3Ks are more closely related to small molecule kinases, such as aminoglycoside kinase (APH) and choline kinases, than ePKs and more distantly related to atypical pseudokinases such as Fam20C and SelO (23)(24)(25). Through quantitative comparisons of the evolutionary constraints acting on diverse PKL-fold enzymes, we previously demonstrated that ePKs share sequence and structural similarity with small molecule kinases in the N-terminal ATP binding lobe, but diverge significantly in the C-terminal substrate binding lobe (21,22,26).…”
Section: Introductionmentioning
confidence: 99%